Output sensitivity of inflation in the euro area: Indirect evidence from disaggregated consumer prices - Annette Fröhling; Kirsten Lommatzsch (Deutsche Bundesbank, 2011)
We investigate output sensitivity of inflation in the euro area through a disaggregated analysis using price indices at the COICOP 4-digit level and compare cyclical sensitivity of a newly created index of cyclically sensitive items (ICSP) with that of headline HICP and core price indices. We also relate the ICSP to the first common factor extracted from the disaggregated prices, which best reflects the common dynamics of the underlying price indices. Our results indicate that two thirds of the items in the euro area HICP are cyclically sensitive. Categories most robustly related to the business cycle are food items (processed and unprocessed), non-durable industrial goods and services related to recreation. Output sensitivity of the ICSP is significantly higher than that of headline inflation. The difference in output sensitivity is most striking between the ICSP and core inflation because of the rather strong cyclical sensitivity of processed and unprocessed food prices (both in prevalence and the estimated parameter of output sensitivity). The index of cyclically sensitive prices is highly correlated with the first common factor. Given the weak factor structure of disaggregated prices, however, we conclude that the domestic business cycle is an important determinant of inflation but it is only one among a number of nearly equally important factors.
Keywords: E31; 330; Output sensitivity; inflation; disaggregated price indices; heterogeneity; euro area; factor analysis